2021
DOI: 10.1017/s0007114521003378
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable factors of 20-year blood pressure trajectories among normotensives and their associations with hypertension : a prospective study

Abstract: Little is known about the impact of modifiable risk factors on blood pressure (BP) trajectories and their associations with hypertension (HTN). We aimed to identify BP trajectories in normotensive Chinese adults and explore their influencing factors and associations with HTN. We used data from 3,436 adults with at least four BP measurements between 1989 and 2018 in the China Health and Nutrition Survey, an ongoing cohort study. We measured BP using mercury sphygmomanometers with appropriate cuff sizes in all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…and other modifiable risk factors (e.g., salt intake, education level and physical activity, etc.) (7,18,19,28,31,(34)(35)(36)(37). More perspective studies are needed to confirm these findings.…”
Section: Discussionmentioning
confidence: 93%
“…and other modifiable risk factors (e.g., salt intake, education level and physical activity, etc.) (7,18,19,28,31,(34)(35)(36)(37). More perspective studies are needed to confirm these findings.…”
Section: Discussionmentioning
confidence: 93%
“…Another study used data from the China Health and Nutrition Survey (CHNS) between 1989 and 2009 to identify 20-year blood pressure trajectories in normotensive adults. Compared with stable low blood pressure levels, the risk of moderate to high increasing trajectories increased by 8–11% for SBP and 5–8% for DBP per 1 cm larger WC, respectively [22]. The present study included both normotensive and hypertensive participants.…”
Section: Discussionmentioning
confidence: 95%
“…Compared with stable low blood pressure levels, the risk of moderate to high increasing trajectories increased by 8–11% for SBP and 5–8% for DBP per 1 cm larger WC, respectively. [ 22 ] The present study included both normotensive and hypertensive participants. We found that the SD, ARV, cumBP, and occurrence of high-risk trajectories in both SBP and DBP increased with higher BMI or WC.…”
Section: Discussionmentioning
confidence: 99%